Chemical Characterisation and Biological Evaluation of Anticancer Properties of Nigerian Plant Extracts and Constituents - Olaleye, Olubusola Omobolanle (2025)
Cancer is presently the second leading cause of mortality worldwide, accounting for approximately 10 million deaths annually. Conventional treatments including surgery, chemotherapy, and irradiation remain dominant, but the exploration of medicinal plants offers promising avenues for innovative cancer therapies. Nigeria's rich biodiversity includes numerous plants used in traditional medicine, many of which remain underexplored for their therapeutic potential. This study investigated the anticancer properties of Nigerian medicinal plants traditionally used for cancer treatment. Preliminary cytotoxicity was evaluated using the brine shrimp lethality assay (BSLA), while growth-inhibitory effects were assessed via the MTT cell viability assay on four cancer cell lines (MCF-7, MDA-MB-231, HUH-7, HeLa) and one non-cancer cell line (MRC-5). To elucidate the mechanisms underlying the growth-inhibitory effects of the active extract on cancer cells, flow cytometry, chemiluminescence, confocal microscopy, and Western blotting were used to assess cell cycle progression, apoptosis induction, DNA damage, cellular morphology, and caspase activation in MCF-7 and MDA-MB-231 cell lines. The bioactive components of the MCL extract were characterised using spectroscopic techniques, including infrared (IR), nuclear magnetic resonance (NMR), and liquid chromatography-mass spectrometry (LC-MS). Additionally, an LC-MS-based metabolomics approach was applied to perform metabolic profiling and identify potential cancer therapy biomarkers. From all the preliminary cytotoxicity screening, the extract of Musanga cecropioides leaves (MCL) was identified to be the most active as it showed potent growth-inhibitory activity against all the cancer cell lines. Of note is the growth-inhibitory effect against MCF-7 cells (GI50 = 3.42±1.80 µg/mL), while also demonstrating 14-fold selectivity towards this cell line relative to non-cancer cell line, MRC-5 cells. In MCF-7 cells, the extract caused G1 phase arrest and possibly G2/M phase arrest in MDA-MB-231 cells. In the two cell lines the extract demonstrated significant apoptotic and necrotic forms of cell death which were corroborated by increased generation of reactive oxygen species (ROS), induction of DNA double-strand breaks in addition to caspase 3/7 activation and disruption of cytoskeletal architecture, particularly in MDA-MB-231 cells. The pro-apoptotic potential of the extract was further confirmed by the cleavage of the apoptotic protein, poly ADP-ribose polymerase 1 (PARP-1) protein which resulted in cleavage of PARP-1 fragments in both cell lysates. Bioassay-guided fractionation resulted in the isolation of 28 spots, with two characterised as docosanoic acid and α-tocopherol. Exploring the combination of these two compounds on MCF-7 and MDA-MB-231 cells suggested that they exhibited synergism in growth inhibition when the cells were treated with α-tocopherol in the presence of fixed concentrations of docosanoic acid, producing combination indices (CI) < 1, particularly at lower concentrations. Furthermore, some of the yet-to-be-identified compounds also displayed significant growth-inhibitory activities while also demonstrating apoptosis-inducing potentials. Metabolomic profiling by LC-MS revealed significant alterations in 97 metabolites and key pathways, including glycerophospholipid, amino acid, and citrate cycle metabolism, critical for cancer cell proliferation. In conclusion, MCL extract exhibited selective anticancer potential against MCF-7 and MDA-MB-231 cell lines leading to the elucidation of the mechanism of action and the isolation of two known bioactive compounds. These results highlight the potential of this extract as a source of chemotherapeutic agents and support its further investigation in preclinical studies for the development of herbal-based cancer therapies.